PENGARUH MOTIVASI TERHADAP KINERJA GURU PADA SD NEGERI SUKOHARJO BELITANG MULYA OKU TIMUR - Deni Kurniawan (STIE Trisna Negara OKU Timur, 2021)
The results showed that the calculation results on the motivation variable where the value of t(count) is greater than t(table) that is 5.128 > 1.8595, then the motivation variable has an influence on the dependent variable, namely Teacher Performance. The value of R (square) or correlation coefficient which indicates the regression model formed by the interaction of variables. Motivation on teacher performance is 0.767 % which is interpreted that the independent variable used in this study shows an influence on the dependent variable of 76.7%, the remaining 23.3% is explained by other factors outside of the independent variables in this study. The t-test is shown from the value of the motivation variable at the value of t(count) 5.128 > t(table) 1.8595 which can be interpreted that the motivation variable has a very strong relationship to teacher performance. Keywords: Motivation, and Teacher Performance.